1999
DOI: 10.1002/(sici)1097-0290(19990305)62:5<593::aid-bit11>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Backward extraction of reverse micellar encapsulated proteins using a counterionic surfactant

Abstract: The back‐extraction of proteins encapsulated in AOT reverse micelles was performed by adding a counterionic surfactant, either TOMAC or DTAB. This novel backward transfer method gave higher backward extraction yields compared to the conventional method with high salt and high pH of the aqueous stripping solution. The protein activity was maintained in the resulting aqueous phase, which in this case had a near neutral pH and low salt concentration. A sharp decrease of the water content was observed in the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Addition of counterionic surfactant causes electrostatic interaction between oppositely charged surfactants, which further results in destabilization of reverse micelles. 22,26 It was observed that addition of CTAB does not improve the BEE significantly. Only 9.42% of protein was back extracted into the stripping phase from the organic phase.…”
Section: Effect Of Stripping Phase Ph and Salt Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of counterionic surfactant causes electrostatic interaction between oppositely charged surfactants, which further results in destabilization of reverse micelles. 22,26 It was observed that addition of CTAB does not improve the BEE significantly. Only 9.42% of protein was back extracted into the stripping phase from the organic phase.…”
Section: Effect Of Stripping Phase Ph and Salt Concentrationmentioning
confidence: 99%
“…Reverse micelles are thermodynamically stable, but under Brownian motion, they constantly collide with each other and this results in temporary fusion of two reverse micelles. 26 Mathew and Juang 46 have reported that a strong interaction between the solubilized proteins and micelles induces the micelle-micelle interaction or reversed micellar cluster formation, resulting in a decrease in back extraction fractions. Hence, the control of micelle-micelle interactions might become an immensely significant factor for the success of back extraction of the proteins.…”
Section: Effect Of Stripping Phase Ph and Salt Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Proteins and enzymes are solubilized into reverse micelles, maintaining their activities and native structures, and can be back-extracted. 11,12 It has been found that the factors such as water content (the molar ratio of water to surfactant, namely, W 0 ) and micelle size, 13 aqueous phase pH and ionic strength, 14 surfactant type and concentration, 15 and cosurfactant 16 affect the protein solubilization and characteristics based on the interactions between reverse micelles and proteins. Moreover, adding proteins to the reverse micelles can alter surfactant self-assembly and phase behavior which can affect the protein efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the extraction mechanism, many efforts have been made to study the effects of various experimental conditions, which include the natures and concentrations of proteins, surfactants, and aqueous electrolytes and the pH of the aqueous phase. [2][3][4][5][6][11][12][13][14][15][16][17][18][19][20][21] It is generally recognized that the electrostatic interactions between a protein and surfactants play an important role in the formation of reverse micelles containing proteins. It has also been claimed that the electrostatic interactions of a protein with a bulk oil/water (O/W) interface play the dominant role in the inclusion of a protein in a reverse micelle at the O/W interface.…”
Section: Introductionmentioning
confidence: 99%